The Language of Belonging - Meinhof, U. author. aut Link
XII, 216 p.
Keywords: This examines a significant aspect of contemporary social life: cultural identities and our linguistic means of constructing them. It combines a theoretical re-assessment of processes of identification with case studies of the discourses of three-generation families living in split-border communities along the former 'Iron Curtain'.